Investing as a mechanism of naturalization in the Developed countries - A. Y. Vakhnyak (Путеводитель предпринимателя, 2020)
On the one hand, investment is a way to increase the available capital, but on the other it is also an opportunity to attract borrowed funds to the needy sectors of the economy. This opportunity is actively used by developed countries, which in exchange for investment in addition to income, can also offer the investor the right to live in their country. The author considers what conditions are put forward by developed countries to investors.